European Women in Mathematics : proceedings of the tenth general meeting, Malta, 24-30 August 2001 - Mezzetti, Emilia; Paycha, Sylvie (World Scientific, 2003)
This volume can be divided into two parts: a purely mathematical part with contributions on finance mathematics, interactions between geometry and physics and different areas of mathematics; another part on the popularization of mathematics and the situation of women in mathematics.